Congenital intestinal lymphangiectasia. A case report - Georgios Mitsiakos; Eftychia Drogouti; Maria Drogouti; Charalampos Doitsidis; Elisabeth Pazarli; Ioannis Spyridakis (Hygeia Press di Corridori Marinella, 2017)
Congenital intestinal lymphangiectasia, first described by Waldmann et al. in 1961, is a rare congenital malformation of the lymphatics, presented with generalized edema, hypoproteinemia and lymphopenia. Diagnosis is based on endoscopy findings and pathology. We present here a case of a male neonate, second child of an indigenous woman, delivered by caesarean section. Prenatally, multiple cystic abdominal masses were identified by ultrasound. The patient was treated successfully with enterectomy and anastomosis. Histopathology revealed primary intestinal lymphangiectasia with no features of malignancy. Intestinal lymphangiectasia is a rare pathology, which should be differentiated while exploring abdominal masses, hypoproteinemia and edema especially in neonates.